1977
DOI: 10.1007/bf01542966
|View full text |Cite
|
Sign up to set email alerts
|

A selective system for hepatoma cells producing gluconeogenic enzymes

Abstract: Gluconeogenesis is a liver-specific pathway which permits the synthesis of phosphorylated sugars from oxaloacetate, pyruvate, amino acids, or trioses. The absolute requirement for glucose or an alternative hexose which characterizes most mammalian cells probably reflects an inablility to perform gluconeogenesis rather than to generate sufficient energy by respiration alone. Cells of diverse histogenetic origins have been tested in glucose-free medium, supplemented with oxaloacetate or with dihydroxyacetone. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…To prepare glucosefree (G Ϫ ) medium, glucose is omitted and serum is extensively dialyzed. G ϩ medium consists of G Ϫ medium supplemented with glucose (2). For reversion analysis, cells were first seeded in a series of dishes in medium supplemented with undialyzed serum and then adapted for 2 to 3 days in G ϩ medium.…”
Section: Methodsmentioning
confidence: 99%
“…To prepare glucosefree (G Ϫ ) medium, glucose is omitted and serum is extensively dialyzed. G ϩ medium consists of G Ϫ medium supplemented with glucose (2). For reversion analysis, cells were first seeded in a series of dishes in medium supplemented with undialyzed serum and then adapted for 2 to 3 days in G ϩ medium.…”
Section: Methodsmentioning
confidence: 99%
“…Gluconeogenesis and Glycolysis in FAO Cells-FAO cells contain all of the gluconeogenic enzymes required for growth and survival in the absence of glucose (11,12), and they can produce glucose from gluconeogenic precursors (13). However, quantitative studies on glucose metabolism in these cells have not been reported.…”
Section: Consequences Of Overexpression Of the Wild-type Andmentioning
confidence: 99%
“…Mutation of Ser-32 to Ala prevents cAMP-dependent phosphorylation of the enzyme (8), while mutation of His-258 to alanine abolishes bisphosphatase activity, since this residue is known to mediate catalysis via a phosphohistidine intermediate (9,10). Since they are capable of producing glucose from 3-carbon precursors (11)(12)(13)(14), cultured rat hepatoma FAO cells were chosen to overexpress the enzyme forms. Thus, the switching mechanism between glycolysis and gluconeogenesis, hypothesized for the bifunctional enzyme and Fru-2,6-P 2 , can be studied.…”
mentioning
confidence: 99%
“…Studies using these clones and the tools of somatic cell genetics (12,23,34) and molecular genetics (4,24,25) have provided evidence that many liver functions are regulated in these cells in a concerted manner. For example, cell lines can be selected which no longer produce the two liver-specific enzymes central to the ability of normal hepatocytes to synthesize glucose (1,2). Loss of the ability of variant cells grow without glucose is accompanied by the loss of other liver functions (e.g., serum albumin production) (23).…”
mentioning
confidence: 99%